Association of oxidative balance score and lung health from the National Health and Nutrition Examination Survey 2007–2012 - Xu, Zhixiao; Xue, Yincong; Wen, Hezhi; Chen, Chengshui (Frontiers in Nutrition, 2023)
Background Oxidative stress is associated with outcomes of chronic lung disease. The oxidative stress-related exposures of diet and lifestyle can be evaluated by the oxidative balance score (OBS), and higher OBS scores indicate more significant antioxidant exposures. But the relationship between OBS and lung health is unknown. Purpose The aim of this study was to explore the association between OBS and lung health (respiratory symptoms, chronic lung disease, and lung function). Methods A series of models, including weighted linear models, weighted logistic regression, and weighted multinomial logistic regression, were performed to assess the associations of OBS with respiratory symptoms, chronic lung disease, and lung function. The models adjusted by age, race/ethnicity, gender, educational background, poverty-to-income ratio, and dietary energy were also performed. Results Cross-sectional data of 5,214 participants from the National Health and Nutrition Examination Survey for the years 2007–2012 were analyzed. For every one-unit increase in OBS, the odds of wheezing/chronic bronchitis decreased by 6%. Increased OBS was associated with higher percent-predicted forced expiratory volume in one second (FEV1) (adjusted mean difference (MD), 0.21%; 95% CI: 0.10–0.32) and percent-predicted forced vital capacity (FVC) (adjusted MD, 0.15%; 95% CI: 0.07–0.24). A significantly lower risk of wheezing/chronic bronchitis was found in participants in the second/third/fourth OBS quartile compared to those in the first OBS quartile (all P for trend < 0.05). Moreover, higher percent-predicted FEV1 and FVC were also found in the third quartile and fourth quartile (all P for trend < 0.05). Furthermore, both dietary and lifestyle components were tightly related to pulmonary outcomes. Many associations were maintained after stratified by sex or after sensitivity analyses. Conclusion Oxidative balance score was negatively correlated with the diagnosis of chronic bronchitis/wheezing/restrictive spirometry pattern and positively correlated with percent-predicted FVC and FEV1. It seems that the higher the OBS score, the better the pulmonary outcomes. The findings highlight the importance of adherence to an antioxidant diet and lifestyle and that it contributes to lung health.